How do batters use visual, auditory, and tactile information about the success of a baseball swing? - Gray, R. (Research Quarterly for Exercise and Sport, 2009)
Bat/ball contact produces visual (the ball leaving the bat), auditory (the "crack" of the bat), and tactile (bat vibration) feedback about the success of the swing. We used a batting simulation to investigate how college baseball players use visual, tactile, and auditory feedback. In Experiment 1, swing accuracy (i.e., the lateral separation between the point of contact and "sweet spot") was compared for no feedback (N), visual alone, auditory alone, and tactile alone. Swings were more accurate for all single-modality combinations as compared to no feedback, and visual produced the greatest accuracy. In Experiment 2, the congruency between visual, tactile, and auditory was varied so that in some trials, the different modalities indicated that the simulated ball contacted the bat at different points. Results indicated that batters combined information but gave more weight to visual. Batting training manuals, which typically only discuss visual cues, should emphasize the importance of auditory and tactile feedback in baseball batting.